ISOLASI DAN IDENTIFIKASI GOLONGAN SENYAWA KIMIA FRAKSI DIETIL ETER DAUN BERUWAS LAUT (Scaevola taccada (Gaertn.) Roxb.) ASAL KABUPATEN PINRANG (SULAWESI SELATAN) - Kosman, Rachmat; Tappang, Kurniati (Fakultas Farmasi UMI, 2012)
Isolation and identification of the chemical compound diethyl ether was done at beruwas laut leaves. Extraction is carried out using methanol and then partitioned with diethyl ether. Fraction of diethyl ether then isolated by column chromatography method using adsorben and n-hexane: ethyl acetate (3:7) as the elution fluid. Then obtained 30 fractions by color and by KLT profiles obtained 16 fractions. dominant fraction with patches further purified by preparative KLT to obtain the pure compound. Tape I at 366 nm UV rays were analyzed by ultraviolet-visible spectroscopy showed maximum absorption at a wavelength of 239.5 nm as measured from wavelength 200-800 nm. Whereas isolates infrared spectroscopic data allow hydroxy, aromatic, and alkyl ketones.Whereas chemical reactions showed positive flavanoid compounds.Key Words : Isolation and identification, fractions of diethyl ether, Scaevola taccada (Gaertn.) Roxb